A New Prescription Emollient Device (PED) For Psoriasis of Sensitive Areas and Folds: A Randomized Prospective Open Trial - Dall'Oglio, Federica; Verzì, Anna Elisa; Guglielmi, Giulia; Zappulla, Sabrina; Micali, Giuseppe (Psoriasis (Auckland, New Zealand), 2024)
Psoriasis affecting sensitive areas and folds represents a therapeutic challenging as the skin in these areas may be more prone to local pharmacological side effects. The aim of this prospective, randomized, open-label study was to evaluate the efficacy and tolerability of a new prescription emollient device (PED) as a cream containing primarily furfuryl palmitate (antioxidant, anti-inflammatory, soothing), tocopherol (antioxidant), and dimethicone (occlusive) for the treatment of psoriasis localized to difficult-to-treat areas. Thirty patients (14M/16F) with mild-to-moderate psoriasis of sensitive areas such as face, vulva, scrotum, pubic area, neck (15 cases), and of folds including axillary fossa, intergluteal cleft, submammary/inguinal folds, and umbilicus (15 cases) were consecutively enrolled and instructed to apply the cream twice daily for 8 weeks. Efficacy was assessed at baseline, at 4 and 8 weeks by measuring the degree of erythema, scaling, infiltration and pruritus using clinical, instrumental and subject-completed Visual Analog Scale (VAS) assessments. At the end of the study, the Investigator Global Assessment (IGA) of efficacy was performed. Statistically significant reductions in erythema, scaling, infiltration, and itching scores were observed at 8 weeks compared to baseline. In addition, IGA efficacy score was clear in 7 cases and almost clear in 4 cases for psoriasis of sensitive areas and clear in 5 cases and almost clear in 4 cases for psoriasis of folds. No relevant side effects were observed in any of the groups. Our results suggest that the tested PED containing antioxidant, anti-inflammatory, soothing and occlusive agents may represent a valid therapeutic option for mild-to-moderate psoriasis of sensitive areas and folds in monotherapy or in combination with pharmacological agents if necessary.